MONTE CARLO SIMULATION OF INTERACTION BETWEEN AN ELECTRON BEAM AND A NANO-SILICON FILM - Elateche, Z.; Aida, M.S. (Journal of Fundamental and Applied Sciences, 2018)
Due to the fundamental role played by the interaction electron-matter in scanning electron microscopy (Electron Beam Induced Current -EBIC- in silicon case), a Monte Carlo calculation model of this interaction applied in silicon nanostructure is presented in the present paper. After a brief introduction to scattering process, our model procedure is described in which electron trajectories in the sample, penetration range (in depth and in spread), backscattered and secondary electron yields (the total electron yield) for nanostructure of silicon are calculated. The variation of this parameters with angle of incidence and impact energy have been studied. The validation of our model is performed by means of comparison with results which been reported by various authors.